Positive electrode for secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery

CN122953535APending Publication Date: 2026-10-20PANASONIC ENERGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580021768.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-18
Filing Date
2025-03-07
Publication Date
2026-10-20

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A positive electrode for a secondary battery comprises a positive electrode compound containing a positive electrode active material, a binder, and a conductive additive. The positive electrode active material contains a lithium-containing composite oxide, the binder contains a fluoropolymer, the degree of polyolefination of the fluoropolymer is less than 0.2, and the conductive additive contains carbon black.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This disclosure claims the benefit of priority to Japanese Patent Application No. 2024-042681, filed on March 18, 2024, with the entire contents of which are incorporated herein by reference. Technical Field

[0003] This disclosure relates to a positive electrode for secondary batteries, a method for manufacturing the same, and a non-aqueous electrolyte secondary battery. Background Technology

[0004] Patent document 1 proposes "a sodium-ion secondary battery comprising a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and a non-aqueous electrolyte having sodium ion conductivity, wherein the positive electrode comprises positive electrode active material particles, a conductive additive and a binder, the positive electrode active material particles having oxide particles that absorb and release sodium ions, and a coating layer covering the oxide particles, wherein the oxide particles comprise an oxide A containing Ni and Mn, the coating layer comprises at least one material B selected from ceramics and carbonaceous materials, and the binder comprises a fluororesin."

[0005] Patent document 2 proposes "a positive electrode for a sodium-ion secondary battery, comprising a positive electrode active material for absorbing and releasing sodium ions, a conductive additive, a binder, and a carboxylic acid, wherein the binder comprises a vinylidene fluoride-based polymer, and the carboxylic acid has at least one of a boiling point and a thermal decomposition point, wherein the lower of the boiling point and the thermal decomposition point exceeds 150°C".

[0006] Patent document 3 proposes "a lithium-ion secondary battery comprising a positive electrode having a positive electrode compound layer, wherein the positive electrode compound layer comprises a layered lithium-nickel composite oxide having a nickel ratio of 80 mol% or more in a metal other than lithium, LiOH, Li2CO3, and a chlorine-containing polyvinylidene fluoride polymer, wherein the content of LiOH in the positive electrode compound layer and the content of Li2CO3 in the positive electrode compound layer are 0.1 wt% or more and 2.1 wt% or less, respectively, the total content of LiOH and Li2CO3 in the positive electrode compound layer is 0.2 wt% or more and 4.2 wt% or less, and the chlorine content in the positive electrode compound layer is 30 μg / g or more and 120 μg / g or less."

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-107713

[0010] Patent Document 2: International Publication No. 2016 / 021405

[0011] Patent Document 3: International Publication No. 2019 / 088171 Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] The positive electrode for a secondary battery comprises a positive electrode slurry layer formed by coating a slurry containing a positive electrode additive (positive electrode slurry) onto the surface of the positive electrode current collector and drying the coating. When the positive electrode additive contains a lithium-containing composite oxide, during the preparation of the positive electrode slurry by mixing the positive electrode additive with a liquid medium, an alkaline component dissolves from the lithium-containing composite oxide into the liquid medium. This alkaline component reacts with a fluoropolymer contained in the positive electrode slurry as a binder, causing the fluoropolymer to polyolefinize. The polyolefinized fluoropolymer, under the influence of van der Waals forces, forms coarse aggregates while simultaneously becoming entangled with carbon black contained in the positive electrode slurry as a conductive additive. As a result, the positive electrode slurry thickens, the effectiveness of the conductive additive decreases, and the positive electrode resistance increases. This thickening of the positive electrode slurry contributes to reduced productivity, increased material loss, and deviations in positive electrode quality due to poor liquid delivery.

[0014] Alkaline components can be partially removed by washing lithium-containing composite oxides with water. However, washing leads to the degradation of lithium-containing composite oxides. From the perspective of minimizing degradation, it is difficult to completely remove alkaline components by washing with water.

[0015] Alternatively, a "coating layer of coated oxide particles" could be formed, as in Patent Document 1, but the coating layer would cause the resistance of the positive electrode to increase, so there is room for improvement.

[0016] Methods for solving problems

[0017] One aspect of this disclosure relates to a positive electrode for a secondary battery, comprising a positive electrode active material, a binder, and a conductive additive, wherein the positive electrode active material comprises a lithium-containing composite oxide, the binder comprises a fluoropolymer, the degree of polyolefination of the fluoropolymer is 0.2 or less, and the conductive additive comprises carbon black.

[0018] Another aspect of this disclosure relates to a non-aqueous electrolyte secondary battery comprising the aforementioned positive electrode, negative electrode, separator, and non-aqueous electrolyte for a secondary battery.

[0019] Another aspect of this disclosure relates to a method for manufacturing a positive electrode for a secondary battery, comprising: a step of preparing a positive electrode slurry comprising a liquid medium and a positive electrode additive dispersed in the liquid medium; a step of preparing a positive electrode current collector and forming a coating film of the positive electrode slurry on the surface of the positive electrode current collector; and a step of drying the coating film by heating it to below 200°C, wherein the positive electrode additive comprises a positive electrode active material, a binder, a conductive additive, and a heteroatom-containing organic additive, wherein the positive electrode active material comprises a lithium-containing composite oxide, the binder comprises a fluoropolymer, and the conductive additive comprises carbon black.

[0020] Invention Effects

[0021] According to this disclosure, it is possible to suppress the thickening of the positive electrode slurry and reduce the positive electrode resistance.

[0022] The novel features of the invention are set forth in the appended claims; however, the invention should be more fully understood, in both its structure and content, together with its other objects and features, by referring to the following detailed description of the accompanying drawings. Attached Figure Description

[0023] Figure 1 This is a simplified perspective view of a portion of a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure. Detailed Implementation

[0024] The following description illustrates embodiments of this disclosure by way of example, but this disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes illustrated, but other numerical values ​​and materials can be applied as long as the effects of this disclosure are achieved. In this specification, the phrase "numerical value A to numerical value B" includes both numerical value A and numerical value B, and can be replaced with "numerical value A or higher and numerical value B or lower." In the following description, when lower and upper limits of numerical values ​​related to specific physical properties, conditions, etc., are illustrated, any of the illustrated lower limits can be arbitrarily combined with any of the illustrated upper limits, as long as the lower limit is not higher than the upper limit. In the following description, when examples of constituent elements or methods are listed, unless specifically stated otherwise, only one of the listed examples can be used, or multiple of the listed examples can be used together.

[0025] This disclosure includes a combination of matters described in any two or more claimed technical solutions selected from the plurality of claimed technical solutions described in the appended scope of protection. That is, as long as no technical contradiction arises, matters described in any two or more claimed technical solutions selected from the plurality of claimed technical solutions described in the appended scope of protection can be combined.

[0026] Non-aqueous electrolyte secondary batteries include lithium-ion secondary batteries that use liquid non-aqueous electrolytes, solid batteries that contain gel electrolytes, and all-solid batteries that use solid electrolytes.

[0027] Non-aqueous electrolyte secondary batteries have a positive electrode, a negative electrode, and a non-aqueous electrolyte. A separator is usually placed between the positive and negative electrodes.

[0028] (positive electrode)

[0029] The positive electrode disclosed herein comprises a positive electrode compound containing a positive electrode active material, a binder, and a conductive additive. The positive electrode compound is typically supported on a positive electrode current collector, forming a positive electrode compound layer. The positive electrode compound layer is formed on the surface of the positive electrode current collector.

[0030] The positive current collector is composed of a sheet-like conductive material. As a positive current collector, a non-porous conductive substrate (such as metal foil) or a porous conductive substrate (such as a mesh, grid, or perforated plate) can be used. The positive electrode flux layer is supported as a film on one or both surfaces of the positive current collector. The material of the positive current collector is not particularly limited; stainless steel, aluminum, aluminum alloys, titanium, etc., can be used.

[0031] The positive electrode active material comprises a lithium-containing composite oxide. From the viewpoint of high capacity and low cost, it is preferable that the lithium-containing composite oxide contains at least Ni. In the lithium-containing composite oxide, the proportion of Ni in the metal elements other than Li can be 80 atomic% or more. Among them, the preferred lithium-containing composite oxide is a lithium nickel oxide (hereinafter also referred to as "composite oxide N") containing Li and Ni, with Ni accounting for 80 atomic% or more in the metal elements other than Li. The proportion of Ni in the metal elements other than Li can be 88 atomic% or more, 90 atomic% or more, or 95 atomic% or more. In the composite oxide N, the proportion of Ni in the metal elements other than Li is less than 100 atomic%, which can be 99 atomic% or less or 98 atomic% or less.

[0032] The positive electrode active material may contain other materials. The proportion of composite oxide N in the positive electrode active material may be, for example, 70% or more by mass, 90% or more by mass, 95% or more by mass, or even 100%.

[0033] Lithium-containing composite oxides are synthesized using lithium compounds as raw materials, and therefore contain alkaline components. Composite oxides (N) with a high Ni content contain even more alkaline components. Composite oxides (N) with Ni comprising more than 90 atomic percent of metals other than Li exhibit particularly high alkalinity. If the alkalinity of the synthesized lithium-containing composite oxide (before water washing) exceeds the permissible range, some of the alkaline components can be removed by water washing to a permissible degree. However, lithium-containing composite oxides (especially composite oxide N) may contain alkaline components both before and after water washing. Alkaline components can be, for example, LiOH, Li₂CO₃, etc., but the almost always contributing factors to the thickening of the cathode slurry are strong bases (primarily LiOH).

[0034] When lithium-containing composite oxides are mixed with a liquid medium (dispersion medium), the alkaline component dissolves into the liquid medium. For example, when the lithium-containing composite oxide contains more than 0.2% by mass of alkaline component, the thickening of the cathode slurry during preparation is significant.

[0035] Thickening begins with the reaction of fluoropolymers, which act as binders in the cathode slurry, with alkaline components, resulting in polyolefination. Polyolefination refers to the formation of double bonds in the fluoropolymers. The polyolefinated fluoropolymers promote the gelation of the cathode slurry over time. Specifically, the polyolefinated fluoropolymers, while entangled with carbon black included as a conductive additive, aggregate and coarsen through van der Waals forces. This aggregation phenomenon makes thickening more pronounced, hinders the formation of conductive pathways based on the conductive additive, and increases the cathode resistance.

[0036] Significant thickening and increased cathode resistance caused by gelation of the cathode slurry need to be avoided. Therefore, conventional lithium-containing composite oxides have undergone processes such as water washing to ensure that the content of alkaline components is less than 0.2% by mass.

[0037] In contrast, the lithium-containing composite oxide contained in the cathode agent of this disclosure may contain 0.2% by mass or more of an alkaline component. Thickening of the cathode slurry is suppressed by a heteroatom-containing organic additive contained in the cathode agent within the cathode slurry. The heteroatom-containing organic additive (hereinafter also simply referred to as "organic additive") adheres to the surface of the lithium-containing composite oxide via heteroatoms. As a result, contact between the surface of the lithium-containing composite oxide and the liquid medium is suppressed, leaching of the alkaline component is suppressed, and reaction between the fluoropolymer and the alkaline component is suppressed. Therefore, the degree of polyolefination of the fluoropolymer contained in the cathode agent layer (cathode agent) stripped from the cathode current collector is low, below 0.2. The degree of polyolefination of the fluoropolymer is preferably below 0.17, more preferably below 0.15.

[0038] The alkaline content in the lithium-containing composite oxide can be 0.2% by mass or more, preferably 0.5% by mass or less, for example, 0.25% by mass or more and 0.4% by mass or more and 0.25% by mass or less and 0.35% by mass or less. When the lithium-containing composite oxide contains more than 0.5% by mass of alkaline content, it is sometimes difficult to suppress the thickening of the cathode slurry even when using organic additives.

[0039] The degree of polyolefination of fluoropolymers can be determined by the following method.

[0040] A sample equivalent to 20g of the positive electrode additive layer (positive electrode additive) stripped from the positive electrode current collector was weighed and mixed with 10mL of N-methyl-2-pyrrolidone (hereinafter also referred to as "NMP") to obtain a mixture. The positive electrode active material was removed from the mixture by centrifugation at 8000rpm for 0.5 hours. Next, the conductive additive was removed by ultracentrifugation at 80000rpm for 11 hours and then at 80000rpm for 4 hours to obtain a fluoropolymer-containing NMP solution. A fluoropolymer membrane was obtained from the fluoropolymer-containing NMP solution by casting. The membrane was dried under reduced pressure at 60°C for 2 hours. The obtained membrane was measured using a Raman spectroscopy apparatus. After baseline correction, the value at 1130cm⁻¹ was calculated. -1 The peak P1, originating from the C=C bond, observed nearby is at 2980 cm⁻¹ -1 The intensity ratio (P1 / P2) of the CH2-originating peak P2 observed nearby is used as the degree of polyolefination.

[0041] The content of alkaline components in lithium-containing composite oxides can be determined by the following method.

[0042] Weigh a sample equivalent to 1.0 g of the positive electrode binder layer (positive electrode binder) stripped from the positive electrode current collector, mix it with 30 mL of deionized water, and shake to dissolve for 30 seconds to obtain a sample solution in which the alkaline component has been dissolved. Then, filter the sample solution and titrate it to pH 8.4 with 1 mol / L hydrochloric acid under N2 atmosphere. Calculate the mass of LiOH (the alkaline component) based on the amount of hydrochloric acid required for titration, and calculate the ratio of the mass of LiOH to the total mass of lithium-containing composite oxides and alkaline components in the sample. It should be noted that the region with pH less than 8.4 is the titration region for weak bases such as Li2CO3.

[0043] Organic additives have flexible organic chains, so even when attached to the surface of lithium-containing composite oxides, they do not easily hinder battery reactions. Therefore, organic additives have little impact on the resistance of the positive electrode. Furthermore, organic additives have low heat resistance, so they can be removed from the positive electrode compound during the manufacturing process through thermal decomposition. The positive electrode compound layer (positive electrode compound) stripped from the positive electrode current collector may or may not contain organic additives containing heteroatoms. From the viewpoint of significantly suppressing the increase in positive electrode resistance, a lower content of organic additives in the positive electrode compound is preferred.

[0044] When the positive electrode additive layer (positive electrode additive) stripped from the positive electrode current collector contains an organic additive, the mass ratio of the organic additive to the lithium-containing composite oxide is preferably 0.1% by mass or less, more preferably 0.07% by mass or less, even more preferably 0.05% by mass or less or 0.03% by mass or less, and can be 0.01% by mass or less. The mass ratio of the organic additive to the lithium-containing composite oxide can, for example, be 0.005% by mass or more.

[0045] The ratio of the mass of the organic additive to the mass of the lithium-containing composite oxide can be calculated based on the thermogravimetric analysis (TGA) results of a sample of the cathode composite layer (cathode composite) stripped from the cathode current collector and the mass of the lithium-containing composite oxide contained in that sample. The TGA can be performed at atmospheric conditions at 5°C / min.

[0046] The decomposition temperature (thermal decomposition temperature) of the organic additive is preferably below 200°C, more preferably below 180°C. The decomposition temperature can be determined by TGA under atmospheric conditions at 5°C / min. Organic additives with a decomposition temperature below 200°C are easily removed from the cathode agent during the manufacturing process of the cathode through thermal decomposition, etc. Therefore, it is easy to reduce the mass ratio of the organic additive to the mass of the lithium-containing composite oxide contained in the cathode agent layer in the finished cathode.

[0047] Organic additives can be Lewis bases. Among Lewis bases, those having nitrogen (N) as a heteroatom are particularly preferred. It is believed that the non-shared electron pairs of nitrogen adsorb onto Lewis acid sites on the surface of lithium-containing complex oxides. Lewis bases containing multiple nitrogen atoms with non-shared electron pairs are particularly preferred in terms of increasing the number of reaction sites. Among Lewis bases having nitrogen as a heteroatom, Lewis bases having nitrogen-containing heterocycles are particularly preferred. The nitrogen-containing heterocycle is preferably, for example, a 5-membered ring, a 6-membered ring, or a 7-membered ring, and preferably has two or more nitrogen atoms. It should be noted that the heteroatom is not limited to N, and can also be S, P, O, etc. Organic additives can contain N and heteroatoms other than N as heteroatoms.

[0048] The nitrogen-containing heterocycle can be a saturated ring without double bonds, but it is preferably aromatic. An aromatic nitrogen-containing heterocycle may contain one or more nitrogen atoms, or more than two. Preferred examples of nitrogen-containing heterocycles include pyrazole rings, imidazole rings, diazine rings, triazine rings, and diazapyridine rings.

[0049] To effectively suppress contact between the liquid medium and the surface of the lithium-containing composite oxide, the organic additive preferably has chain-like organic groups. For example, it may have chain-like organic groups bonded to cyclic atoms of nitrogen-containing heterocycles. The number of carbon atoms in such organic groups may be, for example, 1 to 50, or 5 to 20.

[0050] The molecular weight of the organic additive can be, for example, 50 or more and 1000 or less, 100 or more and 800 or less, or 100 or more and 500 or less. Organic additives with such molecular weights have low thermal decomposition temperatures and sufficient size to effectively suppress surface contact between liquid media and lithium-containing composite oxides.

[0051] Lithium-containing composite oxides can contain Ni, Co, and Mn. Co and Mn contribute to the stabilization of the crystal structure of lithium-containing composite oxides. Lithium-containing composite oxides containing Co and Mn are highly basic and suffer significant degradation due to water washing; therefore, the role of organic additives is particularly important.

[0052] From the perspective of cost reduction and high capacity, the proportion of Co in the metal elements other than Li contained in the lithium-containing composite oxide is preferably 0 atomic% or more and 20 atomic% or less, more preferably greater than 0 atomic% and 5 atomic% or less.

[0053] From the perspective of cost reduction, the proportion of Mn in the metal elements other than Li contained in lithium-containing composite oxides can be more than 1 atomic% and less than 10 atomic%, more than 2 atomic% and less than 5 atomic%, or more than 3 atomic% and less than 5 atomic%.

[0054] Lithium-containing composite oxides can be further incorporated with Al. Al contributes to the stabilization of the crystal structure of lithium-containing composite oxides. Lithium-containing composite oxides containing Co, Mn, and Al are highly basic, thus the role of organic additives is particularly important.

[0055] The proportion of Al in the metal elements other than Li contained in lithium-containing composite oxides can be more than 0.1 atomic% and less than 5 atomic%, more than 0.2 atomic% and less than 3 atomic%, or more than 0.5 atomic% and less than 1 atomic%.

[0056] Lithium-containing composite oxides can be, for example, derived from the formula: Li y Nix M (1-x) O 2-δ (0.8≤x≤1, 0<y≤1.2 and -0.05≤δ≤0.05) represents this. Here, element M can include at least one element selected from Co, Mn, Al, Fe, Ti, Sr, Ca, Zr, W and B. The atomic ratio of Ni, x, can be less than 0.98 or less than 0.95. X increases or decreases due to the charging and discharging of the secondary battery.

[0057] Element M can be represented by the formula: Co 1-x-a-b Mn a Al b (0 < a < 0.05 and 0 < b < 0.05) represents this.

[0058] The thickness of the positive electrode compound layer is not particularly limited; for example, it can be 50 μm or more and 150 μm or less, or 75 μm or more and 125 μm or less. A single positive electrode active material layer can also be formed by multiple layers with different morphologies. For example, two or more layers containing positive electrode active materials with different average particle sizes can be stacked, or two or more layers containing positive electrode active materials of different types or compositions can be stacked.

[0059] The average particle size (D50) of lithium-containing composite oxide particles can be, for example, 1 μm or more and 50 μm or less, or 5 μm or more and 25 μm or less. The average particle size (D50) refers to the median particle size at which the cumulative volume reaches 50% in a volumetric particle size distribution. The volumetric particle size distribution can be determined using a commercially available laser diffraction scattering particle size distribution measuring device.

[0060] The average particle size of lithium-containing composite oxides can be determined based on the cross-section of the cathode composite layer. SEM images of the cross-section are taken with more than 10 lithium-containing composite oxide particles observed. The diameters of more than 10 equivalent circles with the same cross-sectional area as the lithium-containing composite oxide particles are calculated by image processing, and their average value is taken as the average particle size.

[0061] Fluoropolymers that function as binders include vinylidene fluoride (PVDF)-based polymers. Examples of PVDF-based polymers include polymers containing monomers of vinylidene fluoride. Fluoropolymers can be combinations of PVDF-based polymers with other fluoropolymers. PVDF-based polymers can be copolymers of vinylidene fluoride with other monomers. Examples of PVDF-based polymers include polyvinylidene fluoride (PVDF), PVDF-hexafluoropropylene copolymers, etc. PVDF-based polymers preferably contain monomer units derived from vinylidene fluoride in a proportion of 90 mol% or more. The degree of polyolefination of the fluoropolymer before being mixed into the cathode slurry is typically 0.1 or less.

[0062] In the positive electrode mixture, the amount of fluoropolymer relative to 100 parts by mass of the positive electrode active material can be more than 0.1 parts by mass, or more than 0.5 parts by mass, or less than 2.0 parts by mass, or less than 1.2 parts by mass (especially less than 0.98 parts by mass).

[0063] The progress of the polyolefination reaction of fluoropolymers and the degree of formation of coarse aggregates containing carbon black can be affected by the amount of fluoropolymer present. From the viewpoint of reducing the contact frequency between fluoropolymers and alkaline components and effectively suppressing the polyolefination reaction and aggregate formation, in the cathode binder, the amount of fluoropolymer is preferably 0.5 parts by mass or more and less than 1 part by mass (e.g., 0.98 parts by mass or less) relative to 100 parts by mass of the cathode active material, and more preferably 0.5 parts by mass or more and 0.8 parts by mass or less. Under the condition that the polyolefination reaction of fluoropolymers is suppressed by organic additives, the amount of fluoropolymer is also sufficient, for example, 0.98 parts by mass or less relative to 100 parts by mass of the cathode active material. In addition, if the amount of fluoropolymer is 0.5 parts by mass or more relative to 100 parts by mass of the cathode active material, it can fully perform its function as a binder.

[0064] Fluoropolymers can have a weight-average molecular weight of 800,000 or more, 1 million or more, or 1.2 million or more, or less than 2 million or less than 1.8 million. By setting the weight-average molecular weight to 1 million or more, high performance as an adhesive can be achieved with a small amount.

[0065] The conductive additives contained in the positive electrode slurry layer include at least carbon black. The particle morphology of carbon black is such that it readily distributes near the surface of the lithium-containing composite oxide. The heteroatoms of the organic additives interact not only with the surface of the lithium-containing composite oxide but also with functional groups such as OH and COOH groups on the carbon black surface. Therefore, the organic additives promote a more uniform distribution of carbon black on the surface of the lithium-containing composite oxide, improving the reduction effect on the positive electrode resistance. Furthermore, carbon black promotes the adhesion of organic additives to the surface of the lithium-containing composite oxide. By protecting the surface of the lithium-containing composite oxide with carbon black, the Li dissolution caused by the proton exchange reaction between trace amounts of water contained in the positive electrode slurry and the lithium-containing composite oxide is also suppressed, as is the thickening caused by Li dissolution.

[0066] There are no particular limitations on the type of carbon black; any known carbon black can be used. Examples of carbon black include acetylene black, Ketjen black, thermal cracking carbon black, furnace black, and channel black. For example, acetylene black is preferred.

[0067] The degree of formation of coarse agglomerates containing carbon black can be affected by the amount of carbon black present. On the other hand, carbon black plays an important role in reducing the positive electrode resistance. From the viewpoint of reducing the positive electrode resistance and effectively suppressing the formation of agglomerates, in the positive electrode mixture, the amount of carbon black relative to 100 parts by mass of the positive electrode active material is preferably, for example, 0.6 parts by mass or more and less than 1 part by mass (e.g., 0.95 parts by mass or less), and more preferably 0.6 parts by mass or more and 0.8 parts by mass or less. In an environment where organic additives suppress the polyene reaction of fluoropolymers, carbon black helps to more effectively form conductive pathways. Therefore, an amount of carbon black of, for example, 0.95 parts by mass or less relative to 100 parts by mass of the positive electrode active material is sufficient. Furthermore, if the amount of carbon black is 0.6 parts by mass or more relative to 100 parts by mass of the positive electrode active material, the positive electrode resistance can be sufficiently reduced in an environment where organic additives suppress agglomerate formation.

[0068] Carbon black can be used in combination with other conductive additives. Carbon nanotubes (CNTs) are an example of a conductive additive that can be used in combination with carbon black.

[0069] The mass ratio of CNTs contained in the positive electrode mixture layer to the mass of the positive electrode active material is, for example, 0.005% or more and 3% or less, 0.01% or more and 3% or less, or 0.03% or more and 0.5% or less.

[0070] Carbon nanotubes (CNTs) are nanometer-sized carbon materials with a structure consisting of a six-membered ring network of carbon atoms (graphene) wound into a cylindrical shape, exhibiting excellent electrical conductivity. CNTs with a single-layer graphene structure are called single-walled CNTs (SWCNTs). CNTs with multiple layers of graphene structure are called multi-walled CNTs (MWCNTs).

[0071] As a CNT, SWCNT, MWCNT, or both can be used. Among them, SWCNT is fine and soft, and has a strong interaction with aromatic sulfonates (SA) used as dispersants.

[0072] The average diameter of CNTs is preferably 8 nm or less, more preferably 3 nm or less, more preferably 2 nm or less, and may also be less than 1 nm. The average diameter of CNTs is preferably 0.8 nm or more. The average length of CNTs is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 20 μm or less.

[0073] The cathode slurry may contain components other than those mentioned above, as needed. For example, the cathode slurry may contain binders other than fluoropolymers. Examples of such binders include hydrogenated nitrile rubber.

[0074] (The manufacturing method of the positive electrode)

[0075] An example method (hereinafter also referred to as "manufacturing method (M)") for manufacturing a positive electrode for a secondary battery according to the present disclosure will be described. Manufacturing method (M) includes a first step of preparing a positive electrode slurry and a second step of forming a positive electrode flux layer on a positive electrode current collector using the positive electrode slurry. The second step includes a step of preparing a positive electrode current collector and forming a coating film of the positive electrode slurry on the surface of the positive electrode current collector, and a step of heating the coating film to dry it.

[0076] The positive electrode slurry prepared in the first step of manufacturing method (M) comprises a liquid medium and a positive electrode agent dispersed in the liquid medium. The positive electrode agent used is one already described. For example, the positive electrode slurry can be prepared by mixing a positive electrode active material, a fluoropolymer, carbon black, an organic additive, and the liquid medium. The positive electrode active material comprises a lithium-containing composite oxide (preferably a composite oxide N). The positive electrode slurry can be prepared by mixing the positive electrode agent with the liquid medium. The organic additive can be mixed with other components in the form of a solution pre-dissolved in the liquid medium. The mixing method is not particularly limited, and known mixing methods can be used.

[0077] The liquid medium can be an organic solvent or water. N-methyl-2-pyrrolidone (NMP) is preferred as an organic solvent, but alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, ketones such as cyclohexanone, etc., can also be used.

[0078] Organic additives are used to suppress thickening of the cathode slurry. Therefore, they only need to be included in the cathode slurry and do not need to be included in the cathode binder layer. In order to effectively suppress thickening of the cathode slurry, it is preferable that the mass ratio of the organic additive in the cathode slurry to the mass of the lithium-containing composite oxide is, for example, 0.002% by mass or more and 0.3% by mass or less, more preferably 0.02% by mass or more and 0.3% by mass or less, and may also be 0.1% by mass or more and 0.25% by mass or less.

[0079] In the second step, the process of forming a coating film of the positive electrode slurry on the surface of the positive electrode current collector can be performed using coating equipment such as a rod coater, gravure coater, doctor blade coater, roller coater, comma coater, die coater, and lip coater. Alternatively, multiple positive electrode slurries with different compositions can be prepared and coated in two or more layers.

[0080] In the second step, the drying process of the coating is preferably carried out at a temperature below 200°C, for example, at a temperature above 150°C, or even above 180°C. Through the drying process, the liquid medium evaporates, forming an uncalendered coating. At least a portion of the organic additives can be decomposed or evaporated during the drying process and removed from the uncalendered coating.

[0081] Typically, a calendering process is then performed after the coating is not calendered, forming the positive electrode additive layer. The calendering conditions are not particularly limited. The density of the positive electrode active material in the positive electrode additive layer is, for example, 3.3 g / cm³. 3 Above and 4.0 g / cm 3 The following can also be 3.5 g / cm³. 3 Above and 4.0 g / cm 3 the following.

[0082] Depending on the battery structure, the positive electrode flux layer can be formed on only one side of the positive electrode current collector, or it can be formed on both sides of the positive electrode current collector.

[0083] (Non-aqueous electrolyte secondary battery)

[0084] An example of a non-aqueous electrolyte secondary battery of the present disclosure (hereinafter also referred to as "secondary battery (B)") will be described. The secondary battery (B) includes the positive electrode, negative electrode, separator and non-aqueous electrolyte described above.

[0085] The positive electrode of the secondary battery (B) may contain an organic additive attached to the surface of a lithium-containing composite oxide in a cathode layer, but in trace amounts. The mass ratio of the organic additive to the lithium-containing composite oxide is, for example, less than 0.1% by mass. Therefore, the organic additive remaining in the cathode layer hardly increases the resistance of the positive electrode.

[0086] There are no particular limitations on the components other than the positive electrode, and the components used in known non-aqueous electrolyte secondary batteries can also be used. Below, examples of the components of a secondary battery (B) will be explained.

[0087] (positive electrode)

[0088] The positive electrode can be the one described above.

[0089] (negative electrode)

[0090] The negative electrode must at least have a negative current collector. In the case of lithium metal secondary batteries, the negative electrode can use a negative current collector capable of depositing lithium metal or lithium alloy. In the case of lithium-ion secondary batteries, the negative electrode typically contains a negative electrode additive containing a negative electrode active material. The negative electrode additive is supported on the negative current collector, forming a negative electrode additive layer. The negative electrode additive layer is formed on the surface of the negative current collector.

[0091] The negative electrode mixture contains a negative electrode active substance as an essential component. The negative electrode mixture may also contain binders, thickeners, conductive additives, etc., as optional components. These optional components can be those exemplified as components used in the positive electrode.

[0092] The negative electrode mixture layer can be formed by coating a negative electrode slurry, which disperses the components of the negative electrode mixture in a liquid medium (dispersion medium), onto the surface of the negative electrode current collector and then drying it. The dried coating can be calendered as needed. The liquid medium can be any liquid medium used as the positive electrode slurry, as exemplified.

[0093] (Negative electrode active material)

[0094] The negative electrode active material can be selected according to the type of secondary battery (B). An example of a negative electrode active material is a material capable of absorbing and releasing lithium ions. Examples of such materials include carbonaceous materials, Si-containing materials, etc. The negative electrode active material can contain Si-containing materials or be any material containing Si. Metallic lithium, lithium alloys, etc., can be used as negative electrode active materials. The negative electrode can contain one type of negative electrode active material or a combination of two or more.

[0095] Examples of carbonaceous materials include graphite, easily graphitized carbon (soft carbon), and difficult-to-graphitize carbon (hard carbon). A single carbonaceous material can be used, or two or more can be used in combination. Graphite is preferred due to its excellent charge-discharge stability and low irreversible capacity. Examples of graphite include natural graphite, synthetic graphite, and graphitized mesophase carbon particles.

[0096] Examples of Si-containing materials include elemental Si, silicon alloys, silicon compounds (silicon oxides, etc.), and composite materials in which a silicon phase is dispersed within a lithium-ion conductive phase (matrix). Examples of silicon oxides include SiO₂. x Particles. x can be, for example, 0.5 ≤ x < 2, or 0.8 ≤ x ≤ 1.6. As the lithium-ion conducting phase, at least one selected from SiO2 phase, silicate phase and carbon phase can be used.

[0097] The negative current collector can be made of metal foil. The negative current collector can be porous. Examples of materials for the negative current collector include stainless steel, nickel, nickel alloys, copper, and copper alloys.

[0098] (Non-aqueous electrolyte)

[0099] Non-aqueous electrolytes consist of a solvent (a non-aqueous solvent) and a solute dissolved in the solvent. Examples of solutes include lithium salts. Various additives can be added to non-aqueous electrolytes.

[0100] Well-known materials can be used as solvents. Examples of solvents include cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, and chain carboxylic acid esters. Examples of cyclic carbonates include propylene carbonate (PC), ethylene carbonate (EC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC). Chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic acid esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of chain carboxylic acid esters include non-aqueous solvents such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate (EP). One non-aqueous solvent can be used alone, or two or more can be used in combination.

[0101] Examples of lithium salts include lithium salts of chlorinated acids (LiClO4, LiAlCl4, LiB). 10 Cl 10 Lithium salts include those containing fluorine acids (LiPF6, LiPF2O2, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts containing fluorine imides (LiN(FSO2)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), and lithium halides (LiCl, LiBr, LiI, etc.). A single lithium salt can be used, or two or more can be used in combination.

[0102] The concentration of lithium salt in non-aqueous electrolytes can be above 1 mol / L and below 2 mol / L, or above 1 mol / L and below 1.5 mol / L. By setting the concentration of lithium salt within the above range, an electrolyte with excellent ionic conductivity and moderate viscosity can be obtained.

[0103] Non-aqueous electrolytes may contain known additives. Examples of additives include 1,3-propanesulfonate lactone, methyl benzenesulfonate, cyclohexylbenzene, biphenyl, diphenyl ether, fluorobenzene, etc.

[0104] (Diaphragm)

[0105] A separator is positioned between the positive and negative electrodes. The separator preferably has high ion permeability and moderate mechanical strength and insulation. Microporous membranes, woven fabrics, non-woven fabrics, etc., can be used as separators. Examples of separator materials include polyolefins (polypropylene, polyethylene, etc.) and other resins.

[0106] (outer body)

[0107] The electrode assembly and non-aqueous electrolyte are housed within the outer casing (battery housing). The outer casing is not particularly limited and can use any known type. The electrode assembly consists of a positive electrode, a negative electrode, and a separator. The configuration of the electrode assembly is not particularly limited; it can be either wound or stacked. A wound electrode assembly is formed by winding the positive and negative electrodes together with the separator in between. A stacked electrode assembly is formed by stacking the positive and negative electrodes together with the separator in between. The shape of the non-aqueous electrolyte secondary battery is not particularly limited and can be cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0108] Figure 1 This is a simplified perspective view of a secondary battery 10 according to one embodiment of this disclosure, after a partial cross-section. Figure 1 As an example, a square non-aqueous electrolyte battery is shown. Figure 1 The secondary battery 10 shown includes a bottom-shaped cylindrical battery casing 4, and an electrode assembly 1 and a non-aqueous electrolyte (not shown) housed within the battery casing 4.

[0109] Electrode assembly 1 includes a strip-shaped negative electrode, a strip-shaped positive electrode, and a separator disposed between them. The positive electrode is the aforementioned positive electrode. The negative current collector of the negative electrode is electrically connected to the negative terminal 6 disposed on the sealing plate 5 via a negative electrode lead 3. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. The positive current collector of the positive electrode is electrically connected to the back side of the sealing plate 5 via a positive electrode lead 2. That is, the positive electrode is electrically connected to the battery casing 4, which also serves as the positive terminal. The periphery of the sealing plate 5 is fitted into the open end of the battery casing 4, and this fitting is laser-welded. The sealing plate 5 has an injection hole for a non-aqueous electrolyte. The injection hole is plugged with a sealing plug 8 after the non-aqueous electrolyte is injected.

[0110] (Postscript)

[0111] The following technologies are disclosed through the above description.

[0112] (Technology 1)

[0113] A positive electrode for a secondary battery comprises a positive electrode compound containing a positive electrode active material, a binder, and a conductive additive.

[0114] The aforementioned positive electrode active material includes lithium-containing composite oxides.

[0115] The above-mentioned adhesive contains fluoropolymers.

[0116] The degree of polyolefination of the above-mentioned fluoropolymers is below 0.2.

[0117] The aforementioned conductive additives include carbon black.

[0118] (Technology 2)

[0119] According to the positive electrode for a secondary battery described in Technology 1, in the aforementioned positive electrode mixture, the amount of carbon black is 0.6 parts by mass or more and 0.95 parts by mass or less relative to 100 parts by mass of the aforementioned positive electrode active material.

[0120] (Technology 3)

[0121] According to the positive electrode for a secondary battery as described in Technique 1 or 2, in the aforementioned positive electrode mixture, the amount of the fluoropolymer is 0.5 parts by mass or more and 0.98 parts by mass or less relative to 100 parts by mass of the aforementioned positive electrode active material.

[0122] (Technology 4)

[0123] According to any one of the techniques 1 to 3, the positive electrode for a secondary battery contains at least Ni.

[0124] In the above-mentioned lithium-containing composite oxides, Ni accounts for more than 80 atomic% of the metal elements other than Li.

[0125] (Technology 5)

[0126] According to any one of the techniques 1 to 4, the positive electrode for a secondary battery contains 0.2% by mass and 0.5% by mass of an alkaline component.

[0127] (Technology 6)

[0128] According to any one of the techniques 1 to 5, the positive electrode for a secondary battery, wherein the above-mentioned lithium-containing composite oxide is derived from the formula: Li y Ni x M (1-x) O 2-δ (0.8≤x≤1, 0<y≤1.2 and -0.05≤δ≤0.05) means that

[0129] M contains at least one element selected from Co, Mn, Al, Fe, Ti, Sr, Ca, Zr, W, and B.

[0130] (Technology 7)

[0131] According to the positive electrode for a secondary battery described in Technology 6, M is derived from the formula: Co 1-x-a-b Mn a Al b (0 < a < 0.05 and 0 < b < 0.05) represents this.

[0132] (Technology 8)

[0133] According to any one of the techniques 1 to 7, the positive electrode for a secondary battery further comprises an organic additive containing heteroatoms.

[0134] The mass ratio of the above-mentioned organic additive to the mass ratio of the above-mentioned lithium-containing composite oxide is less than 0.1% by mass.

[0135] (Technology 9)

[0136] According to the positive electrode for a secondary battery described in Technology 8, the decomposition temperature of the aforementioned organic additive is below 200°C.

[0137] (Technology 10)

[0138] According to the positive electrode for a secondary battery described in Technique 8 or 9, the aforementioned organic additive is a Lewis base.

[0139] (Technology 11)

[0140] According to any one of the techniques 8 to 10, the positive electrode for a secondary battery has a molecular weight of 50 or more and 1000 or less for the aforementioned organic additive.

[0141] (Technology 12)

[0142] A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte as described in any one of claims 1 to 11.

[0143] (Technology 13)

[0144] A method for manufacturing a positive electrode for a secondary battery, comprising:

[0145] The process of preparing a positive electrode slurry comprising a liquid medium and a positive electrode agent dispersed in the liquid medium.

[0146] The steps of preparing a positive current collector and forming a coating of the positive current collector paste on its surface, and...

[0147] The process of drying the above coating by heating it at a temperature below 200°C;

[0148] The aforementioned positive electrode mixture contains positive electrode active material, binder, conductive additive, and organic additives containing heteroatoms.

[0149] The aforementioned positive electrode active material includes lithium-containing composite oxides.

[0150] The above-mentioned adhesive contains fluoropolymers.

[0151] The aforementioned conductive additives include carbon black.

[0152] (Technology 14)

[0153] According to the manufacturing method of the positive electrode for a secondary battery described in Technology 13, the decomposition temperature of the aforementioned organic additive is below 200°C.

[0154] (Technology 15)

[0155] According to the manufacturing method of the positive electrode for a secondary battery as described in Technique 13 or 14, the aforementioned organic additive is a Lewis base.

[0156] (Technology 16)

[0157] According to any one of the methods for manufacturing a positive electrode for a secondary battery as described in Artificial Intelligence techniques 13 to 15, the molecular weight of the aforementioned organic additive is 50 or more and 1000 or less.

[0158] (Technology 17)

[0159] According to any one of the methods for manufacturing a positive electrode for a secondary battery as described in Artificial Intelligence, the mass ratio of the organic additive to the lithium-containing composite oxide is 0.002% by mass or more and 0.3% by mass or less.

[0160] Example

[0161] The present disclosure is described in detail below based on embodiments, but the present disclosure is not limited to the following embodiments.

[0162] Example 1

[0163] (Preparation of positive electrode slurry SA1)

[0164] A positive electrode slurry SA1 is prepared by mixing a positive electrode active material, polyvinylidene fluoride (PVDF, a fluoropolymer), a pyrazole derivative (PZ1, a Lewis base) with 10 carbon atoms in a chain-like organic group, acetylene black (AB, a conductive additive), and NMP (a liquid medium) in a specified mass ratio. The positive electrode active material, PVDF, PZ1, and AB are the constituent components of the positive electrode mixture. The positive electrode active material uses a composition of LiNi... 0.9 Co 0.04 Mn 0.05 Al 0.01 O2 represents N (NCA) particles, a composite oxide. In the positive electrode mixture, the positive electrode active material, PVDF, PZ1, and AB are mixed in a mass ratio of NCA:PVDF:PZ:AB = 100:0.6:0.01:0.75.

[0165] The weight-average molecular weight of PVDF is 1.4 million. The molecular weight of the pyrazole derivative (PZ1) is approximately 200, and the thermal decomposition temperature of PZ1 is approximately 180°C.

[0166] [Evaluation 1]

[0167] <Determination of viscosity rise rate>

[0168] For the prepared cathode slurry SA1, the viscosity μ0 on the day of preparation and the viscosity μ1 seven days after preparation were measured. Then, the viscosity rise rate was calculated according to the following formula. The viscosity rise rate of each cathode slurry is shown in Table 1. The lower the viscosity rise rate, the better the cathode slurry.

[0169] "Viscosity increase rate (%) = 100 × μ1 / μ0"

[0170] (1) Production of the positive electrode

[0171] A coating film was formed by coating the surface of an aluminum foil (positive current collector) with a positive electrode paste SA1, resulting in a laminate of the aluminum foil and the coating film. Next, the coating film was dried at 180°C, and the laminate was calendered. Thus, a positive electrode A1 comprising an aluminum foil and positive electrode binder layers formed on both sides of the aluminum foil was fabricated.

[0172] [Evaluation 2]

[0173] <Determination of Polyene Degree>

[0174] In the positive electrode A1, the positive electrode flux layer (positive electrode flux) was peeled off from the positive electrode current collector. A sample equivalent to 20g of the positive electrode flux was weighed and mixed with 10mL of NMP. Using the method described above, an NMP solution containing fluoropolymer (PVDF) was obtained from the mixture. A fluoropolymer film was formed from the PVDF NMP solution using the method described above. The wavelength of the film was calculated using a Raman spectroscopy apparatus at 1130cm. -1 The peak P1, originating from the C=C bond, observed nearby is at 2980 cm⁻¹ -1 The intensity ratio (P1 / P2) of the CH2-originating peak P2 observed nearby is used as the polyolefin degree. The polyolefin degree of PVDF contained in cathode A1 is 0.13, as shown in Table 1. It should be noted that the polyolefin degree of PVDF before being mixed into cathode slurry SA1 is less than 0.01.

[0175] <Determination of the alkaline content of N-complex oxides>

[0176] In the positive electrode A1, the positive electrode additive layer (positive electrode additive) is peeled off from the positive electrode current collector. A sample equivalent to 1.0 g of the positive electrode additive is weighed and mixed with 30 mL of deionized water. A sample solution in which the alkali component has been dissolved is prepared using the method described above. The mass of the alkali component is calculated by titration. The mass ratio of the alkali component to the total mass of the composite oxide N contained in the sample (alkali component content) is calculated, and the result is 0.31 by mass.

[0177] (2) Fabrication of the negative electrode

[0178] A negative electrode slurry is prepared by mixing a negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), and water in a specified mass ratio. Graphite is used as the negative electrode active material. Next, the negative electrode slurry is coated onto the surface of a copper foil (negative electrode current collector) to form a laminate containing the copper foil and a coating film formed on the copper foil. After the coating film is dried, the laminate is calendered. This forms a negative electrode containing the copper foil and negative electrode mixture layers formed on both sides of the copper foil.

[0179] (3) Preparation of electrolyte (non-aqueous electrolyte)

[0180] The electrolyte was prepared by adding LiPF6 (lithium salt) to a non-aqueous solvent. The concentration of LiPF6 in the electrolyte was set to 1.0 mol / L. The non-aqueous solvent used was a mixed solvent containing ethylene carbonate (EC): ethyl methyl carbonate (EMC) in a volume ratio of 3:7.

[0181] (4) Manufacturing of secondary batteries

[0182] Leads are installed at the positive electrode A1 and the negative electrode, respectively. Next, the positive electrode, the negative electrode, and the separator are wound into a spiral shape with a separator between the positive and negative electrodes, thereby fabricating an electrode assembly. Next, the electrode assembly and the non-aqueous electrolyte are housed in a cylindrical battery casing. Thus, a cylindrical battery A1 with a positive electrode A1 is fabricated.

[0183] Examples 2-5, Comparative Examples 1-7

[0184] (Preparation of positive electrode slurry SA2, SA3, SC1)

[0185] As shown in Table 1, the mass ratio of organic additives to composite oxide N was varied. Otherwise, cathode slurries SA2, SA3, and SC1 were prepared using the same methods and conditions as those used for preparing cathode slurry SA1. Cathode slurry SC1 does not contain organic additives.

[0186] (Preparation of cathode slurry SC2-SC5)

[0187] CNTs were used instead of AB as conductive additives, and the mass ratio of organic additives to composite oxide N was changed as described in Table 1. Otherwise, positive electrode slurries SC2 to SC5 were prepared using the same method and conditions as those used for preparing positive electrode slurry SA1.

[0188] The average diameter of CNTs is 7 nm and the average length is 10 μm. The mass ratio of positive electrode active material to CNTs is set as positive electrode active material:CNT = 100:0.4.

[0189] (Preparation of positive electrode slurries SA4, SA5, SC6, and SC7)

[0190] As shown in Table 1, the mass ratios of organic additives, AB, and PVDF relative to composite oxide N were changed. Otherwise, cathode slurries SA4, SA5, SC6, and SC7 were prepared using the same methods and conditions as those used for preparing cathode slurry SA1.

[0191] <Determination of viscosity rise rate>

[0192] The viscosity rise rate of each cathode slurry was measured in the same manner as that of slurry SA1. The relative values ​​with the viscosity rise rate of slurry SA1 set to 100 are shown in Table 1. The lower the relative value, the better the cathode slurry.

[0193] Using the same positive electrode slurry as positive electrode A1, positive electrodes A2 to A5 of Examples 2 to 5 and positive electrodes C1 to C7 of Comparative Examples 1 to 7 were prepared.

[0194] Using each positive electrode, batteries A2 to A5 of Examples 2 to 5 and batteries C1 to C7 of Comparative Examples 1 to 7 were manufactured in the same manner as battery A1.

[0195] [Evaluation 3]

[0196] The internal resistance of each battery was measured.

[0197] The relative values ​​of batteries A1 to A3 when the internal resistance of battery C1 is set to 100 are shown in Table 1.

[0198] The relative values ​​of batteries C3 to C5 when the internal resistance of battery C2 is set to 100 are shown in Table 1.

[0199] The relative values ​​of battery A4 when the internal resistance of battery C6 is set to 100 are shown in Table 1.

[0200] The relative values ​​of battery A5 when the internal resistance of battery C7 is set to 100 are shown in Table 1.

[0201] The smaller the relative value of the internal resistance, the better.

[0202] <Measurement of Internal Resistance>

[0203] At 25°C, the battery was charged at a constant current of 0.3 It until the voltage reached 4.2V, and then charged at a constant voltage of 4.2V until the current reached 0.05 It. Using a frequency response analyzer, impedance measurements were performed on the battery at 10kV–0.02Hz within a frequency range. A Cole-Cole plot was constructed based on the results, and the Rs value (i.e., electronic resistance) was obtained from the intersection of the plot with the real axis.

[0204] [Table 1]

[0205]

[0206] A comparison of Examples 1-3 (A1-A3) with Comparative Example 1 (C1) clearly shows that by including organic additives in the positive electrode slurry, the viscosity rise rate is significantly reduced, and the DCIR is also reduced. Furthermore, the more organic additives are used, the lower the viscosity rise rate becomes; however, from the viewpoint of DCIR, it is understood that the amount of organic additives should not be excessive.

[0207] Based on the comparison of Examples 1-3 (A1-A3), Comparative Example 1 (C1), and Comparative Examples 2-5 (C2-C5), it can be understood that the effects of organic additives on reducing the viscosity rise rate of the positive electrode slurry and reducing DCIR are not significant when CNT is used as a conductive additive, but become specifically significant when carbon black is used as a conductive additive.

[0208] Based on the comparison between Example 4 (A4) and Comparative Example 6 (C6), it can be understood that, relative to 100 parts by mass of lithium-containing composite oxide, the fluoropolymer and carbon black are preferably both less than 1 part by mass, more preferably less than 0.8 parts by mass.

[0209] It should be noted that, compared to Comparative Example 1 (C1), a significant effect of the organic additive was also observed in Example 4 (A4). In Example 5 (A5), due to the large amount of binder (fluoropolymer), it is believed that the frequency of polyolefin formation increased, resulting in thickening.

[0210] Industrial availability

[0211] The positive electrode for secondary batteries disclosed herein can be used in high-performance non-aqueous electrolyte secondary batteries.

[0212] The present invention has been described based on currently preferred embodiments, but such disclosure is not intended to be limiting. Various modifications and alterations will undoubtedly be apparent to those skilled in the art upon reading the above disclosure. Therefore, the appended technical solutions should be interpreted as encompassing all modifications and alterations without departing from the true spirit and scope of the invention.

[0213] Explanation of reference numerals in the attached figures

[0214] 1: Electrode assembly, 2: Positive lead, 3: Negative lead, 4: Battery casing, 5: Sealing plate, 6: Negative terminal, 7: Gasket, 8: Sealing plug, 10: Secondary battery (non-aqueous electrolyte secondary battery)

Claims

1. A positive electrode for a secondary battery, comprising a positive electrode compound containing a positive electrode active material, a binder, and a conductive additive. The positive electrode active material comprises a lithium-containing composite oxide. The adhesive comprises a fluoropolymer. The degree of polyolefination of the fluoropolymer is below 0.

2. The conductive additive includes carbon black.

2. The positive electrode for a secondary battery according to claim 1, wherein, In the positive electrode mixture, the amount of carbon black is 0.6 parts by mass and 0.95 parts by mass or less, relative to 100 parts by mass of the positive electrode active material.

3. The positive electrode for a secondary battery according to claim 1, wherein, In the positive electrode mixture, the amount of the fluoropolymer is 0.5 parts by mass or more and 0.98 parts by mass or less, relative to 100 parts by mass of the positive electrode active material.

4. The positive electrode for a secondary battery according to claim 1, wherein, The lithium-containing composite oxide contains at least Ni. In the lithium-containing composite oxide, Ni accounts for more than 80 atomic% of the metal elements other than Li.

5. The positive electrode for a secondary battery according to claim 1, wherein, The lithium-containing composite oxide contains 0.2% by mass and less than 0.5% by mass of an alkaline component.

6. The positive electrode for a secondary battery according to claim 1, wherein, The lithium-containing composite oxide is derived from the formula: Li y Ni x M (1-x) O 2-δ This indicates that 0.8 ≤ x ≤ 1, 0 < y ≤ 1.2, and -0.05 ≤ δ ≤ 0.

05. M contains at least one element selected from Co, Mn, Al, Fe, Ti, Sr, Ca, Zr, W, and B.

7. The positive electrode for a secondary battery according to claim 6, wherein, M is derived from: Co 1-x-a-b Mn a Al b This indicates that 0 < a < 0.05 and 0 < b < 0.

05.

8. The positive electrode for a secondary battery according to claim 1, wherein, The positive electrode mixture also contains organic additives containing heteroatoms. The mass ratio of the organic additive to the lithium-containing composite oxide is less than 0.1% by mass.

9. The positive electrode for a secondary battery according to claim 8, wherein, The organic additive decomposes at a temperature below 200°C.

10. The positive electrode for a secondary battery according to claim 8, wherein, The organic additive is a Lewis base.

11. The positive electrode for a secondary battery according to claim 8, wherein, The organic additive has a molecular weight of 50 or higher and 1000 or lower.

12. A non-aqueous electrolyte secondary battery comprising the positive electrode, negative electrode, separator, and non-aqueous electrolyte as described in claim 1.

13. A method for manufacturing a positive electrode for a secondary battery, comprising: The process of preparing a positive electrode slurry comprising a liquid medium and a positive electrode agent dispersed in the liquid medium. The steps of preparing a positive current collector and forming a coating film of the positive current collector slurry on the surface of the positive current collector, and... The process of drying the coating by heating it at a temperature below 200°C; The positive electrode mixture comprises a positive electrode active material, a binder, a conductive additive, and an organic additive containing heteroatoms. The positive electrode active material comprises a lithium-containing composite oxide. The adhesive comprises a fluoropolymer. The conductive additive includes carbon black.

14. The method for manufacturing a positive electrode for a secondary battery according to claim 13, wherein, The organic additive decomposes at a temperature below 200°C.

15. The method for manufacturing a positive electrode for a secondary battery according to claim 13, wherein, The organic additive is a Lewis base.

16. The method for manufacturing a positive electrode for a secondary battery according to claim 13, wherein, The organic additive has a molecular weight of 50 or higher and 1000 or lower.

17. The method for manufacturing a positive electrode for a secondary battery according to claim 13, wherein, The ratio of the mass of the organic additive to the mass of the lithium-containing composite oxide is more than 0.002% by mass and less than 0.3% by mass.

Citation Information

Patent Citations

  • Sodium ion secondary battery and positive electrode active material particle

    JP2017107713A

  • Loxoprofen or salt thereof and pharmaceutical composition including herbal medicine

    JP2024042681A

  • Positive electrode for sodium ion secondary cell, and sodium ion secondary cell

    WO2016021405A1

  • Lithium ion secondary battery

    WO2019088171A1